Nuclear Governance Assessing Effectiveness and Enhancing International Cooperation: Tata Kelola Nuklir Menilai Efektivitas dan Meningkatkan Kerja Sama Internasional - Nishonov , Abdulloh Ubaydulloh o’g’li (Universitas Muhammadiyah Sidoarjo, 2024)
This article explores the legal regulation of atomic energy, focusing on its historical evolution, current status, and effectiveness. It addresses gaps in understanding regarding the adequacy of existing regulations and the extent of international cooperation. Employing a multifaceted approach, including documentary analysis and interviews, the study assesses legislative frameworks and institutional mechanisms. Findings reveal the complexities of atomic energy governance and underscore the importance of international cooperation in enhancing regulatory compliance. This research provides valuable insights for policymakers and stakeholders, facilitating informed strategies to strengthen nuclear governance and ensure safe and sustainable atomic energy utilization. Highlights: Comprehensive assessment of legal regulations governing atomic energy. Importance of international cooperation in enhancing regulatory compliance. Implications for strengthening nuclear governance and promoting sustainability. Keywords: Atomic Energy, Legal Regulation, International Cooperation, Governance, Agreements